En helig källas teologi före och efter reformationen : Helene Kilde i Tisvilde och Erich Hansens »Fontinalia Sacra« 1650 - Arvidsson, Bengt (Kirkehistoriske Samlinger, 1991)
The point of departure for the article lies in certain usages of a cult-like character connected with a spring of water in Tisvilde, North Sealand (the »Spring of Helene«) where acts of healing were widely believed to occur in post-Reformation times as well as earlier - and increasingly so in the first part of the 17th Century. As a contribution to official endeavours to supervise these goings-on and provide visitors with sound understanding, Erich Hansen, the rector of Græsted, in 1650 published a book entitled »Fontinalia Sacra« in which a doctrine of the God-given curative properties of water is developed within the wider context of a theology of nature. The article analyzes this complex of ideas, uncovers its roots in orthodox Lutheran as well as Paracelsic & thinking, and describes later developments connected with springs in Northern countries and ideas about healing by water and herbs.